2022
DOI: 10.3389/fpsyg.2022.1021969
|View full text |Cite
|
Sign up to set email alerts
|

What are the key drivers to promote entrepreneurial intention of vocational college students? An empirical study based on structural equation modeling

Abstract: In order to alleviate the increasing employment pressure of vocational college students, the current study is an attempt to explore the factors of entrepreneurial intention affecting vocational college students. The study investigates whether entrepreneurial self-efficacy and attitude mediate this relationship between creativity and entrepreneurial intentions using the theory of planned behavior (TPB). In particular, this research also examines whether risk propensity moderates the relationship. An empirical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 123 publications
0
11
0
Order By: Relevance
“…Firstly, innovation in research perspectives. This paper discusses the influencing factors and the interaction mechanism between the vocational college students’ intention to use online learning continuously, filling the gap that most current relevant researches focus on general college education and ignore vocational college students ( Niu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, innovation in research perspectives. This paper discusses the influencing factors and the interaction mechanism between the vocational college students’ intention to use online learning continuously, filling the gap that most current relevant researches focus on general college education and ignore vocational college students ( Niu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the survey reveals that students at vocational colleges have a hard time maintaining focus while studying online for extended periods of time ( Panigrahi et al, 2018 ; Baber, 2021 ; Soria-Barreto et al, 2021 ). Consequently, one of the methods to boost the vocational college students’ intention to continue using online learning systems is to enhance learners’ self-efficacy and decrease students’ anxiety level regarding the usage of online learning systems ( Niu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…As far as the nature of the entrepreneurial opportunity, there are two competing views, i.e., the discovery and the creation point of view (Edelman and Yli-Renko, 2010 ; Kuckertz et al, 2017 ; Niu et al, 2022 ). Moreover, yet for university students, the creation point of view is more appropriate than the discovery point of view for examining university students' ability of EOI (Munoz et al, 2011 ; Chen and Tao, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of PC in explaining EI is obvious since previous research in the field of business shows that entrepreneurs differ from no entrepreneurs in terms of essential PC ingredients (Bockorny and Youssef-Morgan, 2019 ; Chen and Tao, 2021 ). For those who would be entrepreneurs, the positive effect of self-efficacy on EI is well-documented (e.g., Gao and Qin, 2022 ; Niu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous research support the notion that INT contributes either directly or indirectly to student SAT in a online learning context (Niu et al, 2022b). In addition to the variables of motivation, course structure, and teacher facilitation/knowledge, Baber (2020) shown that INT is the most influential factor in determining students' perceived learning outcomes, which in turn impacts student SAT.…”
Section: Int and Satmentioning
confidence: 96%